2018
DOI: 10.3917/ecop.214.0097
|View full text |Cite
|
Sign up to set email alerts
|

Déploiement du très haut débit et création d’entreprises dans les zones rurales : une évaluation du programme Auvergne Très Haut Débit

Abstract: Depuis près de 15 ans, les pouvoirs publics déploient internet dans les territoires ruraux qui, faute de rentabilité, sont délaissés par les opérateurs privés. Ces investissements publics sont motivés par une volonté d’assurer l’équité territoriale mais aussi de stimuler l’attractivité économique de ces territoires. Afin d’analyser l’efficacité de ces politiques sur ce deuxième objectif, ce travail évalue l’impact des premières années du programme « Auvergne Très Haut Débit » sur la création d’entreprises dans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…In contrast to the findings described, the evaluation work of Duvivier et al [51] of the Auvergne très haut débit programme in France concludes that the deployment of fiber and high speed has not significantly stimulated the creation of enterprises, having affected positively only to the creation of companies in specific sectors: hostelry; public administration, education, health and social work; and other activities in the services sector. While the deployment of fiber and high speed does not appear to be sufficient on its own to drive rural economic development, it may be a lever for development when certain conditions, related to the territorial economic context and design of digital policy, are met [51]. From the opposite perspective, the existence of faster internet technologies can even increase the urban-rural digital divide, as they are more expensive and difficult to obtain in rural areas [52].…”
Section: Broadband As An Essential Requirementmentioning
confidence: 59%
“…In contrast to the findings described, the evaluation work of Duvivier et al [51] of the Auvergne très haut débit programme in France concludes that the deployment of fiber and high speed has not significantly stimulated the creation of enterprises, having affected positively only to the creation of companies in specific sectors: hostelry; public administration, education, health and social work; and other activities in the services sector. While the deployment of fiber and high speed does not appear to be sufficient on its own to drive rural economic development, it may be a lever for development when certain conditions, related to the territorial economic context and design of digital policy, are met [51]. From the opposite perspective, the existence of faster internet technologies can even increase the urban-rural digital divide, as they are more expensive and difficult to obtain in rural areas [52].…”
Section: Broadband As An Essential Requirementmentioning
confidence: 59%
“…Several works have concluded that broadband has a positive effect on firm location decisions (Kim & Orazem, 2017) and that limited connectivity strongly hurts rural businesses (Whitacre & al., 2014-b), particularly in the creative sector (Townsend & al., 2017). A majority of studies, however, find very limited (Duvivier & al., 2018;Kandilov & Renkow, 2010) or insignificant effects on firm location (Canzian & al., 2019;Mack & Wentz, 2017;Whitacre & al., 2014-a). Conley & Whitacre (2016) even show that nonmetropolitan counties with the largest increases in broadband experience the strongest drop in entrepreneurship and the number of creative workers because broadband allows individuals to be better aware of alternative job opportunities in neighboring metropolitan areas.…”
Section: Differences Across Locationsmentioning
confidence: 99%
“…In almost all cases, previous studies have concluded that broadband impact is significantly heterogeneous across industries. Overall, positive effects are generally found in a large range of services (Audretsch & al., 2015;Duvivier & al., 2018;Gurney, 2012;Hasbi, 2017;Shideler & Badasyan, 2012). While some concerns have been raised about broadband impact on the retail trade sector (with local businesses potentially negatively affected by heightened competition with online retailers), most studies also find positive effects on the number of retail establishments.…”
Section: Differences Across Industriesmentioning
confidence: 99%
See 2 more Smart Citations